TINJAUAN KESULITAN GURU DALAM KEGIATAN LABORATORIUM PADA PEMBELAJARAN IPA TERPADU DI SMPN SE-KECAMATAN TIGO NAGARI KABUPATEN PASAMAN - Fitri, Haftika; Mulyati, Mulyati; Megahati, Megahati (STKIP PGRI Sumbar, 2013)
ABSTRACT In science education laboratory activities in one of the important activities junior high school, so the implementation of laboratory activities is expected to run well. The various of efforts is repaired to improve skill of teachers through the upgrade and the MGMP activities, this examination to aims to find out difficulties wich is faced by the teachers of science, implementation and result of laboratory in the junior high school Tigo Nagari Pasaman. This research is descriptive the samples in this research were the teachers of science integrated all of distract Tigo Nagari who has done laboratory activities that amounted 10 people (total of sampling). A survey was spreaded to the teachers of science at junior high school in all of distract Tigo Nagari before that it was tested to the teachers of science at 1 Simpati junior high school that ammounted 4 people. The data was processed through descriptive analysis by using a percentase formula. Based on data analysis was found 80,30% about the teachers difficulties in laboratory activities with high category,its mean that the teachers of science at junior high school Tigo Nagari were not realize difficultyes in laboratory activities.